Analysis of the Determining Factors of IKIP Budi Utomo Students’ Motivation in Taking the Teaching Profession - Kusmawati, Wiwik; Kurniawan, Choirul; Sudarsono, Sudarsono; Irawan, Dedy (JUPE : Jurnal Pendidikan Mandala, 2023)
The purpose of this study was to determine the motivational factors of students choosing the teaching profession at IKIP Budi Utomo students. This study uses quantitative methods with descriptive statistical data analysis techniques. The sampling technique used purposive sampling. Collecting research data using a questionnaire. The factors that influence the motivation of Budi Utomo IKIP students to choose the teaching profession are as follows: Desire (60.55%); Needs (77.38%); Personality (76.89%); Ability (66.96%); Well-being (67,23%); and Social Environment (67.82%).